Perempuan, Tubuhnya dan Narasi Perkosaan dalam Ideologi Patriarki : Kajian Hermeneutik Feminis Terhadap Narasi Perkosaan Tamar dalam II Samuel 13:1-22 - Suryaningsi Mila (Asosiasi Teolog Indonesia, 2016)
Tamar’s rape is narrated in a conflict of interest among Amnon and Absalom. Tamar’s rape was just the beginning of the conflict among Absalom and Amnon who fought for the throne as the symbol of power. In fact, Tamar was a muted victim. Therefore, it needs a critical eye such as a feminist hermeneutic approach to re-read and reinterpret this story. Feminist hermeneutic critical is a tool to explore the hidden stories especially about women’s experiences on violence and oppression. This approach will help us to produce a theological reconstruction on the experience of Tamar’s oppression and her struggle. Through hermeneutic feminist critical, the story of Tamar and her pain will be the main concern. Tamar was no longer cry for her wounds and trauma. She will have a chance to tell her bitter experience. She will have a space to speak up and share her pain. The story of Tamar as a survivor will be remembered and celebrated as the standpoint to fight against violence in our present context. This approach also guides the church to re-thinking and re-frame its theological understanding deals to the increasing of sexual abuses against women and children. Some findings on Tamar’s story will be a reference to deconstruct the patriarchal culture and to build a theology of equality among men and women.